Antifungal Activity of Rhein and Aloe‐Emodin from Rheum palmatum on Fish Pathogenic Saprolegnia sp. Issue 1 (13th July 2016) - Yao, Jia‐Yun; Lin, Ling‐Yun; Yuan, Xue‐Mei; Ying, Wen‐Lin; Xu, Yang; Pan, Xiao‐Yi; Hao, Gui‐Jie; Shen, Jin‐Yu; Wu, Jin‐Chun; Ye, Ting; Ge, Pei‐Hong
Abstract: Saprolegnia infections cause severe economic losses among freshwater fish farming. In this study, two known compounds, rhein and aloe‐emodin, were isolated from Rheum palmatum, and the in vitro inhibitory activity of both compounds against mycelial growth and spore germination of Saprolegnia was tested. Both rhein and aloe‐emodin were able to decrease Saprolegnia mycelial growth and spore activity in all tested concentrations after exposure for 48 h. Complete inhibition of mycelial growth was observed at 20 mg/L for rhein and at 50 mg/L for aloe‐emodin, while spore germination was 100% prevented at 16 and 40 mg/L for rhein and aloe‐emodin, respectively. Because rhein showed stronger in vitro anti‐ Saprolegnia activity, it was further tested in vivo to measure the prevention and treatment efficacy on Saprolegnia infection of grass carp. Its acute activity to grass carp was also evaluated. The results revealed that exposure to rhein at 20 mg/L for 7 d could prevent 93.3% of infections by Saprolegnia in abraded grass carp, while 67.7% of infected fish could be recovered by treatment with rhein. The 48‐h median lethal concentration (48 h‐LC50 ) to grass carp was 148.5 mg/L, which is about 7.4 times the effective dose indicating the safety for the use of rhein. This study suggests that rhein has promising anti‐ Saprolegnia activity and may be an option in preventing and controlling Saprolegnia infection.